Marine control over negative power law scaling of mass wasting events in chalk sea cliffs with implications for future recession under the UKCP09 medium emission scenario. Issue 10 (14th April 2018) - Gilham, Jamie; Barlow, John; Moore, Roger
Abstract: Coastal cliff erosion represents a significant geohazard for people and infrastructure. Forecasting future erosion rates is therefore of critical importance to ensuring the resiliency of coastal communities. We use high precision monitoring of chalk cliffs at Telscombe, UK to generate monthly mass movement inventories between August 2016 and July 2017. Frequency–magnitude analysis of our inventories demonstrate negative power law scaling over 7 orders of magnitude and, for the first time, we report statistically significant correlations between significant wave height (Hs ) and power law scaling coefficients (r 2 values of 0.497 and 0.590 for β and s respectively). Applying these relationships allows for a quantitative method to predict erosion at the site based on Hs probabilities and sea level forecasts derived from the UKCP09 medium emission climate model (A1B). Monte‐Carlo simulations indicate a range of possible erosion scenarios over 70 years (2020–2090) and we assess the impact these may have on the A259 coastal road which runs proximal to the cliffs. Results indicate a small acceleration in erosion compared with those based on current conditions with the most likely scenario at the site being 21.7 m of cliff recession by 2090. However, low‐probability events can result in recession an order of magnitude higher in some scenarios. In the absence of negative feedbacks, we estimate an ~11% chance that the A259 will be breached by coastal erosion by 2090. Copyright © 2018 John Wiley & Sons, Ltd. Abstract : Coastal cliff erosion represents a significant geohazard for people and infrastructure. By constraining negative power law parameters by environmental conditions a probabilistic recession model was developed to predict future coastal cliff recession. This method provides coastal managers with a tool to evaluate potential risk to infrastructure through time to facilitate effective planning and mitigation.